The automation of the procedures of educational progress assessment as a method of education quality improving; The 9th International Forum on on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Lepustin A. V. Aleksey Vladimirovich; Spitsyn V. G. Vladimir Grigorievich; Ilyukhin B. V.; Smyslova E. V. (2014, 2014)
Title screen